Utilization of Solar Street Lights as Lighting Facilities in Tourist Places: Pemanfaatan Lampu Penerangan Jalan Umum Bertenaga Surya Sebagai Sarana Penerangan di Tempat Wisata - Ari Fadli; Daru Tri Nugroho; Arief Wisnu Wardhana; Gito Sugiyanto; Hari Prasetijo; Widhiatmoko Herry Purnomo (Yayasan Ahmar Cendekia Indonesia, 2022)
Hutan Pinus Limpakuwuswhich is located on the southern slope of Mount Slamet is located at an altitude of about 750 meters above sea level (MDPL). The Limpakuwus Pine Forest has limited access to electricity from the PLN network, so there are still many locations at night or cloudy skies, so these locations have limited access, this causes the manager to use generators to turn on the lights in order to provide the electricity needed for electricity. provide information on the location in the Limakuwus Pine Forest tourist spot. The interview and survey method started this service activity, the interview aimed to determine the need for the number of spots (spots), to get lighting and a survey to determine the location of the lamp installation. equipment, and manufacture of solar powered PJU light poles and their installation. The results of these activities include increasing knowledge, skills of residents in the field of fabrication and installation of solar-powered PJU lamps with the installation of 2100Lm 20 Watt LED lights, 5V/40Watt Solar Panels and 3.2V/32 Ah batteries at predetermined locations, as well as increased ease of use. running activities at night at that location. Abstrak Hutan Pinus Limpakuwus yang berada di lereng selatan Gunung Slamet itu berada pada ketinggian sekitar 750 meter di atas permukaan laut (MDPL). Hutan Pinus Limpakuwus memiliki akses listrik terbatas dari jaringan PLN, sehingga masih banyaknya lokasi yang malam hari atau kondisi langit mendung, maka lokasi tersebut memiliki akses yang terbatas hal ini menyebabkan pihak pengelola menggunakan genset guna menghidupkan lampu dalam rangka menyediakan sarana kebutuhan listrik yang digunakan untuk memberikan penerangan pada lokasi di tempat wisata Hutan Pinus Limakuwus tersebut. Metode wawancara dan survey mengawali kegiatan pengabdian ini, wawancara bertujuan untuk menentukan kebutuhan jumlah titik (spot), untuk mendapat penerangan dan survey guna menentukan lokasi pemasangan lampu Metode pelaksanaan kegiatan meliputi: survey lokasi, identifikasi dan solusi masalah, perencanaan kegiatan, perhitungan kebutuhan bahan dan peralatan, dan pembuatan tiang lampu PJU bertenaga surya dan pemasangannya. Hasil kegiatan antara lain peningkatan pengetahuan, ketrampilan warga di bidang fabrikasi dan instalasi lampu PJU bertenaga surya dengan terpasangnya lampu LED 2100Lm 20 Watt, Solar Panel 5V/40Watt dan battery 3.2V/32 Ah pada lokasi yang telah di tentukan sebelumnya, serta peningkatan kemudahan dalam menjalankan aktivitas dimalam hari pada lokasi tersebut.